Glycemic Control, Hand Activity, and Complexity of Biological Signals in Diabetes Mellitus - Hsien-Tsai Wu; Gen-Min Lin; Bagus Haryadi; Chieh-Ming Yang; Hsiao-Chiang Chu (Complexity)
Both glycemic control and handgrip strength affect microvascular function. Multiscale entropy (MSE) of photoplethysmographic (PPG) pulse amplitudes may differ by diabetes status and hand activity. Of a middle-to-old aged and right-handed cohort without clinical cardiovascular disease, we controlled age, sex, and weight to select the unaffected (no type 2 diabetes, n=36), the well-controlled diabetes (HbA1c < 8%, n=22), and the poorly controlled diabetes (HbA1c ≥ 8%, n=22) groups. MSEs were calculated from consecutive 1,500 PPG pulse amplitudes of bilateral index fingertips. The small-,  medium-, and large-scale MSEs were defined as the average of scale 1 (MSE1), scales 2–4 (MSE2–4), and scales 5–10 (MSE5–10), respectively. Intra- and intergroups were compared by one- and two-sample t-tests, respectively. The dominant hand MSE5–10 was lower in the poorly controlled diabetes group than the well-controlled diabetes and the unaffected (1.28 versus 1.52 and 1.56, p=0.019 and 0.001, resp.) groups, whereas the nondominant hand MSE5–10 was lower in the well- and poorly controlled diabetes groups than the unaffected group (1.35 and 1.29 versus 1.58, p=0.008 and 0.005, resp.). The MSE1 of dominant hand was higher than that of nondominant hand in the well-controlled diabetes (1.35 versus 1.10, p=0.048). In conclusion, diabetes status and hand dominance may affect the MSE of PPG pulse amplitudes.